2013
DOI: 10.1038/srep01604
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional graphene foam as a biocompatible and conductive scaffold for neural stem cells

Abstract: Neural stem cell (NSC) based therapy provides a promising approach for neural regeneration. For the success of NSC clinical application, a scaffold is required to provide three-dimensional (3D) cell growth microenvironments and appropriate synergistic cell guidance cues. Here, we report the first utilization of graphene foam, a 3D porous structure, as a novel scaffold for NSCs in vitro. It was found that three-dimensional graphene foams (3D-GFs) can not only support NSC growth, but also keep cell at an active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
540
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 579 publications
(562 citation statements)
references
References 28 publications
(56 reference statements)
10
540
0
2
Order By: Relevance
“…Polyethylenimine (PEI) modifies the surface of GO sheets and thus makes it ready for cellular gene delivery through covalent conjugation and electrostatic interaction [58] for plasmid DNA (pDNA) stacking. GO is attached covalently to the linear chain [35] and branched chain [59]. PEI is thus used for high-quality transfection effectiveness containing low cytotoxicity than pDNA/PEI complexes.…”
Section: Gene Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Polyethylenimine (PEI) modifies the surface of GO sheets and thus makes it ready for cellular gene delivery through covalent conjugation and electrostatic interaction [58] for plasmid DNA (pDNA) stacking. GO is attached covalently to the linear chain [35] and branched chain [59]. PEI is thus used for high-quality transfection effectiveness containing low cytotoxicity than pDNA/PEI complexes.…”
Section: Gene Deliverymentioning
confidence: 99%
“…FeO nanoparticles provided GO with multifunctionality and multimodality for assorted organic and medicinal applications [62]. Antiinflammatory drug delivery of ibuprofen has been reported by applying chitosan-containing GO [35].…”
Section: Small Molecule Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that three-dimensional graphene foams (3D-GF) can not only support NSCs growth, but also keep cells at an active proliferation state with regulation of Ki67 expression than that of two-dimensional graphene films. Meanwhile, phenotypic analysis indicated that 3D-GFs can enhance the NSCs differentiation towards astrocytes and especially neurons [106] .…”
Section: Bio-interface Of Carbon Nanotube and Graphene Based Materialmentioning
confidence: 99%
“…Western Blot analysis of Ki67 expression on 2D graphene films and 3D-GFs. The Data are presented as mean 卤 standard error (s. e. m.), *p < 0.05, **p< 0.01 [106] . Table 1.…”
Section: Figure 12mentioning
confidence: 99%